Strengthening Inclusive Village Governance through Gender Equality Education to Encourage Women's Leadership Participation in Village Government - Komarudin, Komarudin (Politeknik Siber Cerdika Internasional, 2025)
This study examines the persistent underrepresentation of women in village governance in Indonesia and evaluates the effectiveness of gender equality education as a transformative intervention to strengthen women’s leadership participation. The research aims to measure changes in gender awareness, leadership self-efficacy, and women’s substantive involvement in village decision-making, while also identifying mechanisms that support institutional change. An explanatory sequential mixed-methods design with a quasi-experimental approach was employed across 72 villages in three districts, combining pre- and post-intervention surveys, difference-in-differences analysis, and qualitative exploration through interviews, focus groups, and observations he 12-week education program generated substantial improvements: gender awareness increased by 40.3 points, women’s leadership self-efficacy rose by 31.1 points, and participation indicators including speaking frequency, proposal acceptance, and representation in village structures improved significantly compared to control villages. Follow-up at 12 months showed sustained institutional changes through gender-responsive regulations, increased budgets for women’s programs, and active gender task forces. These findings indicate that gender equality education can shift norms, enhance agency, and catalyze institutional reforms necessary for inclusive village governance. The study concludes that embedding gender equality education within village systems is crucial to advancing women’s leadership and strengthening grassroots democratic practices.